New understandings of fathers' experiences of grief and loss following stillbirth and neonatal death: A scoping review. (December 2019) - Jones, Kerry; Robb, Martin; Murphy, Sam; Davies, Alison
Highlights: Existing research shows that perinatal loss has a profound psychological impact on fathers. It is evident that there is a need for more cross-cultural research in this area. There is a need to understand how perinatal loss impacts on men's health and wellbeing. Abstract: Objective: To report on research conducted on men's experiences of grief and loss following stillbirth and neonatal death in high-income, Western countries. Design: This review was guided by the following research questions: 1. The impact of perinatal death for men 2. The meaning of the loss for a father's sense of identity 3. The extent to which men were able to express grief while supporting their partners and, 4. how men's experience of grief was mediated by the support and care received by health professionals. Data sources: We searched the following databases: Medline; PsychINFO; CINAHL to identify relevant articles published from the year 2000 onwards. The searches were run between 1/04/2018 and 8/4/2018. Review methods: A scoping review was conducted of nursing, psychological, medical and social science databases using these key words: fathers' grief, men's grief, perinatal loss and death, stillbirth and neonatal death. Results: Studies indicated that men reported less intense and enduring levels of psychological outcomes than women but were more likely to engage in avoidance and coping behaviours such as increased alcohol consumption. Men felt that their role was primarily as a 'supportive partner' and that they were overlooked by health professionals. Conclusions: Further research is needed on men's experience of grief following perinatal death, especially on their physical and mental well-being. Impact: This review addressed the problem of the lack of knowledge around paternal needs following perinatal death and highlighted areas which researchers could usefully investigate with the eventual aim of improving care for fathers.